Recycling of Electrode Materials from Spent Lithium-Ion Batteries to Develop Supercapacitor Devices - Mesbah, Yasmine (AUC Knowledge Fountain, 2023)
Recently, there has been a rapid expansion in the utilization of lithium-ion batteries (LIBs) due to the propagation of portable electronic devices, electric vehicles, and renewable energy storage systems. Despite the plentiful advantages provided by LIBs, concerns have emerged regarding resource depletion and the environmental impact associated with their widespread use. The lack of essential resources such as lithium, cobalt, and nickel, along with the difficulties associated with managing battery waste, necessitates the development of sustainable strategies that encompass the entire lifecycle of LIBs. Recycling has arisen as a promising solution to combat these challenges and promote a more circular economy for LIBs. Among the various recycling approaches, the recovery and reuse of cathode materials from spent LIBs has gained considerable attention. In parallel, supercapacitors have encountered considerable growth as a substitute energy storage solution to LIBs. Supercapacitors, also known as ultracapacitors, offer distinct advantages such as high-power density, rapid charge/discharge rates, and exceptional cycling stability. Integrating LIB recycling and supercapacitor technology presents a compelling sustainability and resource efficiency opportunity. This thesis examines the recycling of spent LIBs and the use of the recovered materials to construct supercapacitor devices. The research encompasses various aspects, including the characterization of materials, evaluation of electrochemical performance, optimization of electrode fabrication techniques, and assessment of overall device performance. The findings and insights from this research can open the way for a more environmentally friendly and resource-efficient approach to LIBs and supercapacitors, ultimately facilitating the transition towards a sustainable energy storage realm.